2019
DOI: 10.1093/jas/skz069
|View full text |Cite
|
Sign up to set email alerts
|

Ergot alkaloid exposure during gestation alters: II. Uterine and umbilical artery vasoactivity1

Abstract: Mention of trade name, proprietary product of specified equipment does not constitute a guarantee or warranty by the USDA and does not imply approval to the exclusion of other products that may be available. USDA is an equal opportunity provider and employer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
1
21
0
1
Order By: Relevance
“…Tall fescue seed was fed individually to supply 1.77 mg animal −1 d −1 of ergovaline and ergovalinine for E+ and the same weight of E− tall fescue seed was fed to supply 0 mg animal −1 d −1 of ergovaline and ergovalinine. Ergovaline and ergovalinine concentrations fed in this study were based on previous research and is detailed in Britt et al (2019). Ewes were individually penned into stalls (1.8 × 0.5 × 0.91 m) at 0700 and individually fed their respective treatment diet for 90 min.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Tall fescue seed was fed individually to supply 1.77 mg animal −1 d −1 of ergovaline and ergovalinine for E+ and the same weight of E− tall fescue seed was fed to supply 0 mg animal −1 d −1 of ergovaline and ergovalinine. Ergovaline and ergovalinine concentrations fed in this study were based on previous research and is detailed in Britt et al (2019). Ewes were individually penned into stalls (1.8 × 0.5 × 0.91 m) at 0700 and individually fed their respective treatment diet for 90 min.…”
Section: Experimental Designmentioning
confidence: 99%
“…Ewes within each group were fed equal amounts of TMR and seed daily to maintain similar feed intake across all treatments. Feed intake and body weight changes during the study are reported in Britt et al (2019). On day 133 of gestation, ewes underwent terminal surgery where fetuses were removed and euthanized.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, solute carrier family 22 member 9 (SLC22A9; also known as OAT7) experienced a 5-fold increase in the cotyledon from E+/E+ ewes and was previously thought to be liver-specific [62]. It has been hypothesized that ergot alkaloids or metabolites may cross the placental barrier [7] but no research is available documenting the presence of these compounds in the fetus or which transport systems may be involved if placental transport exists. It was previously proposed that the downregulation of certain transport systems may augment fetal exposure to environmental toxicants during pregnancy [63].…”
Section: Gene Ontology and Kegg Pathway Analysismentioning
confidence: 99%